Peluang dan Tantangan Transformasi Digital dalam Pembelajaran Pendidikan Islam di MTs Hang Nadim Batam - Deassy Arestya Sakhsita; Anis Nirmala Patmawati; Aulya Putri; Fathir Rahman Muzakhy; Muhammad Yusuf Budiarto; Patimah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The acceleration of digital technology stimulates a fundamental transformation in Islamic Religious Education (PAI), requiring madrasahs to optimize technological utility without reducing Islamic values. This study analyzes the opportunities and challenges of digital transformation in PAI learning at MTs Hang Nadim Batam. Utilizing a descriptive qualitative method, data were gathered through observations and interviews with the headmaster, teachers, and students, then analyzed using an interactive model. The findings indicate that digitalization successfully expands access to learning resources, enriches instructional media, enhances flexibility, and escalates students' digital literacy. Nevertheless, implementation encounters determinant obstacles, including a disparity in teachers' digital competence, challenges in students' self-regulation, internet connectivity limitations, and the urgency of digital supervision. Ultimately, the success of this digital transformation heavily depends on the integrated readiness of human resources, mature supporting infrastructure, firm institutional policies, and the collaborative synergy of all school stakeholders.